Factors affecting early and late period outcomes in patients undergoing surgical repair due to biliary tract injury - Çoğal, İbrahim; Yavuz, Burak; Kaycı, Yunus; Topal, Uğur; Aydın, İshak; Saritas, Ahmet Gokhan; Dalci, Kubilay; Eray, İsmail Cem; Akcam, Atilgan Tolga; Ülkü, Abdullah (Frontiers in Surgery, 2025)
AimCholecystectomy is the most common elective abdominal surgery globally. With the advent of laparoscopy, laparoscopic cholecystectomy has become the gold standard. However, this has also led to an increase in biliary tract injuries, a complication with high morbidity and mortality that requires a multidisciplinary treatment approach. This study aims to identify factors influencing postoperative outcomes in patients undergoing surgical repair for biliary tract injuries.Materials and methodThis study included 66 patients referred to the General Surgery Department of Çukurova University Medical Faculty for biliary tract injuries between January 2005 and June 2022, all of whom underwent hepaticojejunostomy. Demographic data, pre- and post-operative lab values, imaging, and anastomosis types were recorded and analyzed. Early and long-term postoperative outcomes were examined, using the McDonald classification for long-term follow-up.ResultsOf the 66 patients, 18 (27.3%) were male, and 48 (72.7%) were female, with a mean follow-up of 105 ± 58 months. Early postoperative complications developed in 28 patients (42.4%). Diabetes and culture positivity were significantly associated with wound infections. Elevated pre- and post-repair ALP and GGT levels were significantly associated with poorer long-term outcomes according to the McDonald classification. Vascular injury was significantly associated with isolated ALP-GGT elevation. Anastomotic stricture developed in 8 patients (12.1%). Of these, 2 (3%) were successfully managed with balloon dilationConclusionBiliary tract injury is a serious complication post-cholecystectomy, requiring a multidisciplinary approach and follow-up in a hepatobiliary center. Surgeon experience and local risk factors are crucial in managing these injuries.